Representation of Social Criticism of Post-1965 Historical Reality in the Novel My Name is Alam by Leila S. Chudori - Sefia; Resdianto Permata Raharjo (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the representation of social criticism regarding the historical reality of the post-1965 era in Leila S. Chudori’s novel Namaku Alam. This study employs a qualitative method based on Alan Swingewood’s sociological approach to literature, which focuses on literature as a social document or a reflection of the times. The data source for this study is the novel Namaku Alam by Leila S. Chudori, published by Kepustakaan Populer Gramedia in 2023. The research data consists of dialogues, sentences, and paragraphs collected using documentation techniques and analyzed using hermeneutic techniques. The hermeneutic process involved the stages of identification, classification, codification, interpretation, and data presentation. The research findings indicate that the novel Namaku Alam represents a critique of the post-1965 historical reality through various repressive practices carried out by the state. First, state-sanctioned terror and persecution are represented through arbitrary arrests, forced disappearances, and intensive surveillance of individuals and families deemed to have ties to the PKI. Second, the manipulation of history is represented through the state’s control of historical narratives, whether through the construction of official history, public spaces, or the education system. Third, restrictions on freedom of expression are represented through pressure on academics and journalists, a strict licensing system, and the banning of book distribution. These findings indicate that the novel Namaku Alam serves not only as a work of fiction but also as a medium for social criticism that reflects the historical reality of post-1965 Indonesia.